(untitled) (MINDEN Journal of History and Archaeology, 2026)
This paper studies the economic and cultural transformations of early Myanmar society by analyzing Pyu silver coins discovered from the ancient city of Sriksetra (a UNESCO World Heritage Site), which flourished between the 2nd century AD to the 9th century AD. The study emphasizes how the Pyu people transitioned from a barter system to a stamped silver coinage system to facilitate, stability and convenience in trade. Srivatsa, Bhadrapitha, conch, sun, and moon motifs on Pyu coins represent religious, symbolic iconography, and royal symbolism that integrate with the Indian culture and indigenous traditions and beliefs. This paper analysis the existence of strong regional economic, trade networks and the existence of shared culture within Pyu city states by comparing the four types of coins discovered at Sriksetra with other coin types discovered from other Pyu ancient cities as Halin, Beikthano, and Pinle (Maingmaw). Keywords: Srivatsa; Bhadrapitha; Sriksetra coins; Pyu coinage; early Myanmar society